Reviews in computational chemistry. - Lipkowitz, Kenny B.; Boyd, Donald B. (Reviews in Computational Chemistry., 1997)
Not only a major reference work for sale to the library market, Reviews in Computational Chemistry is now a purchase by individuals due to the explosive growth in the use of computational chemistry throughout many scientific disciplines. In an instructional and nonmathematical style, these books provide an access to computational methods often outside a researcher's area of expertise. Volumes 9 & 10 represent the next two volumes in the successful series designed to help the chemistry community keep current with the many new developments in computational techniques. Many chapters are written a.